Visualizing fungicide action: an in vivo tool for rapid validation of fungicides with target location HOG pathway. Issue 3 (27th September 2018) - Bohnert, Stefan; Neumann, Hendrik; Thines, Eckhard; Jacob, Stefan
Abstract: BACKGROUND: The mitogen‐activated protein kinase MoHog1p was fused with a green fluorescent protein (GFP) in the filamentous fungus Magnaporthe oryzae . The MoHOG1::GFP mutant was found to be an excellent tool visualizing in vivo fungicide‐dependent translocation of MoHog1p into the nucleus. Validation of pathway specificity was achieved by generating fluorescence‐labelled MoHog1p in the ΔMohik1 'loss of function' mutant strain. RESULTS: GFP‐labelled MoHog1p expressed in the wildtype and in ΔMohik1 demonstrates that fludioxonil is acting on the HOG pathway and even more precisely that fungicide action is dependent on the group III histidine kinase MoHik1p. GFP‐tagged MoHog1p translocated into the nucleus upon fungicide treatment in the MoHOG1::GFP mutant within seconds, but did not do so in the ΔMohik1/HOG1::GFP mutant. CONCLUSION: Here, we developed a rapid in vivo tool for fluorescent‐based validation of fungicides targeting the HOG‐signaling pathway. Furthermore, using the fluorescent mutants generated in this study, we are able to visualize that fungicide action is dependent on the histidine kinase MoHik1p but operates in a different mechanism of pathway activation compared to osmotic stress. © 2018 Society of Chemical Industry Abstract : This article presents a rapid in vivo tool for fluorescent‐based validation of fungicides with direct reference to the target location.